Exogenous macroeconomic shocks and their propagation in Bosnia and Herzegovina - Bojan Baskot (Graduate Institute of International and Development Studies, 2016)
Vector autoregressive (VAR) models are commonly used for macroeconomic analyses. However, there are several reasons why this tool has not been applied to the case of Bosnia and Herzegovina. As Bosnia and Herzegovina has a currency board system, I use a VAR model with exogenous variables (VARX) and consider two exogenous shocks: interest rates for countries in the Eurozone and remittances. My analysis confirms that Bosnia and Herzegovina is a small open economy highly dependent on foreign aid and remittances, and has no autonomous monetary policy because of the currency board system.
Keywords: 330